Store Environment Assessment (SEA) Tool: Design and validation of a food environment audit protocol. (30th September 2020) - Jago, E; Minaker, L; Mah, C L
Abstract: Background: Unhealthy food environments are key factors in diet-related disease risk. Many audit methods have been designed for the retail food environment, but weaknesses of existing methods include: validity in study methods and design, and heterogeneity in adaptation and analysis methods. This paper describes the development and validation of a novel protocol for designing store audit instruments - the Store Environment Assessment (SEA) Tool. Methods: This research involved four steps: 1. a scoping review of consumer food environment audit tools; 2. classify key variables from the literature; 3. use the variables to design a protocol for development of audit instruments tailored to local contexts and research questions; and 4. validate the protocol by designing and validating a sample audit tool based on Canada's Food Guide (2019). Results: Variables from the literature included: Product (availability, variety, size, reference), Price, Promotion, Placement-accompanied by: definition, type of variable, range of values, scale of measurement, and measurement outcome. The protocol has seven steps: identify dietary guideline criteria; conduct content analysis; define setting; align research questions with scale and scope; variable selection; audit tool design; and validation strategy. The protocol was used to design a store audit instrument for Canadian jurisdictions, based on Canada's Food Guide, and validated against the gold standard, Nutrition Environment Measures Survey (NEMS). Discussion: The SEA protocol can strengthen researchers and practitioners' capacity to use structured guidelines to develop geographically and socio-demographically relevant Store Environment Assessments, and avoid heterogeneity arising from ad hoc adaptations of tools such as NEMS. Our methodological approach can support greater consistency, feasibility, and rigour of food environment audits for diverse public health research and practice objectives. Key messages: Researchers and practitioners will be able to utilize the SEA tool protocol, using jurisdictional food and nutrition criteria, to better assess 4Ps related to food, in retail food environments. The variables and measurement outcomes included in the SEA tool protocol will support public health practitioners in developing relevant interventions to support healthy consumer food purchasing.